2022
DOI: 10.1159/000520891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Expanded Hemodialysis with Theranova® in Patients with COVID-19

Abstract: <b><i>Introduction:</i></b> Cytokine storm control is the main target for improving severe COVID-19 by using immunosuppressive treatment. Effective renal replacement therapy (RRT) could give us an advantage removing cytokines in patients with RRT requirements superimposed on COVID-19. <b><i>Methods:</i></b> This is a prospective observational study in COVID-19 patients who required hemodialysis (HD). Patients were assigned to online hemodiafiltration (OL-HDF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In our study, the mean IL-6 was 5.70 pg/mL, which is a similar baseline concentration to previous studies [13]. One observational study showed that expanded hemodialysis improves survival and effectively removes cytokines in patients with COVID-19 [22]. Further studies should reveal whether expanded HD could effectively remove inflammatory cytokines in patients with severe infection.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the mean IL-6 was 5.70 pg/mL, which is a similar baseline concentration to previous studies [13]. One observational study showed that expanded hemodialysis improves survival and effectively removes cytokines in patients with COVID-19 [22]. Further studies should reveal whether expanded HD could effectively remove inflammatory cytokines in patients with severe infection.…”
Section: Discussionsupporting
confidence: 89%